Maternal Vitamin D and Its Role in Amniotic Membrane Thickness in Premature Rupture of Membranes - Hafis Novyan; Rajuddin Rajuddin; Niken Asri Utami (Indonesian Socety of Obstetrics and Gynecology, 2026)
AbstractObjective: To examine the correlation between maternal serum vitamin D levels and amniotic membrane thickness in cases of premature rupture of membranes (PROM).Methods: This analytical cross-sectional study was conducted from July to November 2022 at Dr. Zainoel Abidin General Hospital, the Universitas Syiah Kuala Research Laboratory, and Prodia Banda Aceh Laboratory. A total of 30 women with term PROM who met the inclusion and exclusion criteria were enrolled. Serum vitamin D levels were measured using Electrochemiluminescence Immunoassay (ECLIA), while amniotic membrane thickness was assessed histologically using hematoxylin Eosin (HE) staining. Spearman’s correlation test was performed with a 95% confidence level.Results: Thirty mothers with PROM were included, with a mean age of 31.37 ± 6.8 years. Vaginal delivery was the predominant mode of delivery (53.3%). The mean serum vitamin D level was 20.25 ng/mL (range: 8.5–42.5 ng/mL), and the mean amniotic membrane thickness was 82.51 µm (range: 28.69–227.8 µm). No significant correlation was observed between serum vitamin D levels and amniotic membrane thickness (r = −0.029; p = 0.878).Conclusion: There was no significant correlation between maternal serum vitamin D levels and amniotic membrane thickness in cases of PROM.Keywords: amnion, pregnancy, premature rupture of membranes, thickness of the membranes, vitamin D.